In search of the federal spirit : new comparative empirical and theoretical perspectives - Burgess, Michael, 1949- (Oxford : Oxford University Press, 2013)
'In Search of the Federal Spirit' is a major examination of the theory and practice of federal state formation in the post-Cold War era. It introduces the concept of the federal spirit as a means of exploring the emergence of a range of new political models.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Keywords: Federal government